A Green Route for the Preparation of Aliphatic Polyesters via Lipase‐catalyzed Prepolymerization and Low‐temperature Postpolymerization. Issue 6 (25th September 2012) - Vouyiouka, Stamatina N.; Topakas, Evangelos; Katsini, Adamantia; Papaspyrides, Constantine D.; Christakopoulos, Paul
Abstract Lipase‐catalyzed polycondensation of two biobased diacids, 1, 12‐dodecanedioic acid and 1, 14‐tetradecanedioic acid, with 1, 8‐octanediol was achieved using immobilized Lipase B from Candida antarctica. The procedure resulted in partially renewable prepolymers, while poly(octylene adipate) from petroleum‐based adipic acid was also synthesized for comparison reasons, revealing a dependence of the enzymatic polymerization degree on monomer composition. The prepolymers were further submitted to bulk postpolymerization at temperatures in the vicinity of their melting point under flowing nitrogen. The intrinsic viscosity increase was found up to 12%, with no significant impact on the polyesters thermal properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>